Case of idiopathic portal hypertension complicated with autoimmune hepatitis. Issue 9 (15th May 2013) - Abe, Kazumichi; Takahashi, Atsushi; Sato, Yu; Okai, Ken; Katsushima, Fumiko; Monoe, Kyoko; Kanno, Yukiko; Saito, Hironobu; Ohira, Hiromasa
Abstract : We report a case of idiopathic portal hypertension (IPH) complicated with autoimmune hepatitis. A 60‐year‐old woman was admitted to our hospital with esophageal and gastric varices in February 2010. Abdominal ultrasonography and computed tomography showed splenomegaly and collateral veins without evidence of liver cirrhosis. Laboratory examinations and liver biopsy indicated that the esophageal and gastric varices were caused by IPH. She underwent endoscopic injection sclerotherapy and partial splenic embolization. Two years after these therapies, laboratory examinations showed liver dysfunction with elevated levels of aspartate aminotransferase (180 IU/L), alanine aminotransferase (190 IU/L), γ‐glutamyl transpeptidase (159 IU/L) and immunoglobulin G (2609 mg/dL). The titer of antinuclear antibodies was 1:320 and its pattern was homogeneous and speckled. Histological examination revealed plasma cell/lymphocyte infiltration and interface hepatitis in the portal tract. Based on these findings, a diagnosis of autoimmune hepatitis accompanied by IPH was made. After treatment with prednisolone (20 mg/day), liver functions were normalized immediately. Overlapping of IPH and AIH is extremely rare, but the present case is interesting considering the etiology of IPH because an autoimmune mechanism is thought to be involved in the pathogenesis of IPH.